Analysis of Students’ Abilities in Solving Story Problems with an Ethnomathematics Context Based on Polya’s Steps - Raihani; Noor Fajriah; Rahmita Noorbaiti (Universitas Teknokrat Indonesia, 2025)
Problem-solving ability is an important mathematical ability for finding solutions to problems. One strategy that can improve students' problem-solving abilities is by involving them in solving story problems. This study aims to analyze students' abilities in solving story problems associated with the context of ethnomathematics based on Polya's steps. Using a quantitative descriptive approach method with a focus on fifth-grade students of an elementary school in Banjarmasin City. Data were collected through test instruments and response questionnaires. The results of the study showed that the abilities of fifth-grade students of an elementary school in Banjarmasin City were included in the category of lacking in solving story problems with the context of ethnomathematics according to Polya's steps. The average score of students at the stage of understanding the problem was included in the category of less, at the stage of devise a plan was included in the category of very less, at the stage of carry out the plan was included in the category of sufficient, and at the stage of look back was included in the category of very less. Therefore, a more systematic learning strategy is needed to improve students' abilities in solving story problems with the context of ethnomathematics.